Methylation patterns in dysplasia in inflammatory bowel disease patients. (2nd June 2020) - Rosa, Isadora; Silva, Patrícia; da Mata, Sara; Magro, Fernando; Carneiro, Fátima; Peixoto, Armando; Silva, Marco; Sousa, Helena T.; Roseira, Joana; Parra, José; Barosa, Rita; Vieira, Ana; et al.
Abstract: Background and aims: Inflammatory Bowel Disease (IBD) with colonic involvement increases colorectal cancer risk. However, the distinction between IBD related and sporadic dysplasia in IBD patients is difficult. Some data favors the importance of abnormal DNA methylation in IBD-related carcinogenesis. We aimed to define methylation patterns in patients with colonic cancer or dysplasia diagnosis following an IBD diagnosis. Methods: Multicentric cross-sectional study-91 samples from colonic mucosa with/without dysplasia from 9 patients with IBD-related dysplasia/cancer and 26 patients with IBD and sporadic dysplasia/cancer were included. Methylation patterns of CpG islands in the promoter regions of 67 genes were studied by Methylation-specific Multiplex Ligation-dependent Probe Amplification. Results: Mean age at IBD diagnosis: 42 ± 16 years;at dysplasia diagnosis: 56 ± 14 years. Twenty-ninepatients had ulcerative colitis. Twenty-five patients had at least 1 lesion endoscopically described as adenoma-like, 4 at least 1 non-adenoma like, 3 had cancer and 3 had dysplasia in flat mucosa. No patient had both adenoma-like and non-adenoma-like lesions. Patients with an IBD-related lesion were significantly younger at IBD diagnosis ( p = .003) and at dysplasia/cancer diagnosis ( p = .039). Promoter methylation of IGF2, RARB, ESR1, CHFR, CDH13, WT1, GATA5, WIF1 genes was significantly associated to dysplasia/cancer; methylation of MSH6, TIMP3 was significantly associated to IBD-related dysplasia/cancer. Promoter methylation of MSH6, MSH3, RUNX3, CRABP1, TP73, RARB, CDH13, PAX5, WT1, THBS1, TP53, SFRP1, WIF1, APAF1, BCL2 genes was significantly associated to active IBD. Conclusions: Methylation analysis, namely of MSH6, may contribute to the classification of dysplastic lesions in IBD– to be further tested in prospective studies.